2004
DOI: 10.1136/bjo.2003.031948
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating keratoplasty: indications over a 10 year period

Abstract: Aims: To determine the indications for penetrating keratoplasty (PK) at the Corneoplastic Unit and Eye Bank, UK, a tertiary referral centre, over a 10 year period. Methods: Records of all patients who underwent PK at our institution between 1990 and 1999 were reviewed retrospectively. Of the 1096 procedures performed in this period, 784 records were available for evaluation (72%). Results: Regrafting was the most common indication, accounting for 40.9% of all cases. Keratoconus was the second most common indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
1
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(107 citation statements)
references
References 32 publications
6
87
1
13
Order By: Relevance
“…In a study by Nagra et al (12) , the most common indication for PK among patients who developed WD was also keratoconus, followed by Fuch's endothelial dystrophy and pseudophakic bullous keratopathy. This is in contrast to the most common indication for corneal transplantation performed in the United States and United Kingdom, which is graft failure (13,14) . Other indications include pseudophakic or aphakic bullous keratopathy, Fuch's endothelial dystrophy, keratoconus, and viral keratitis (13,14) .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a study by Nagra et al (12) , the most common indication for PK among patients who developed WD was also keratoconus, followed by Fuch's endothelial dystrophy and pseudophakic bullous keratopathy. This is in contrast to the most common indication for corneal transplantation performed in the United States and United Kingdom, which is graft failure (13,14) . Other indications include pseudophakic or aphakic bullous keratopathy, Fuch's endothelial dystrophy, keratoconus, and viral keratitis (13,14) .…”
Section: Discussionmentioning
confidence: 89%
“…This is in contrast to the most common indication for corneal transplantation performed in the United States and United Kingdom, which is graft failure (13,14) . Other indications include pseudophakic or aphakic bullous keratopathy, Fuch's endothelial dystrophy, keratoconus, and viral keratitis (13,14) . In another retrospecti ve case series of 19 traumatic dehiscence with corneal grafts that underwent repair In Australia, the most common indication for the original graft was keratoconus (9) .…”
Section: Discussionmentioning
confidence: 89%
“…[1][2][3] Despite high success rates for penetrating keratoplasty (PK) for keratoconus, which have been calculated to be 98.9% at 46 months followup 4 and 93.7% at 13.8 years, 5 complications such as graft failure and keratoconus recurrence occur in a small minority of cases. [5][6][7][8][9] Previous histopathological studies on recurrent keratoconus have shown the presence of tissue abnormalities consistent with keratoconus, such as breaks in the epithelial basement membrane and Bowman's layer, abnormal keratocytes, and stromal thinning.…”
Section: Introductionmentioning
confidence: 99%
“…Table 5 provides information on important indications for keratoplasty in different geographical locations. [35][36][37][38][39][40][41][42][43][44] As the table shows, the important causes of corneal blindness (based on indications of keratoplasty) in Established economies are pseudophakic bullous keratopathy, keratoconus, failed grafts, and corneal dystrophy. In contrast, in less developed economies corneal scar and active keratitis are the most common indications for penetrating keratoplasty.…”
Section: Causes Of Corneal Blindnessmentioning
confidence: 99%